Chemical diversity of microbial volatiles and their potential for plant growth and productivity - Kanchiswamy, Chidananda Nagamangala; Malnoy, Mickael; Maffei, Massimo E. (Frontiers in Plant Science, 2015)
Microbial volatile organic compounds (MVOCs) are produced by a wide array of microorganisms ranging from bacteria to fungi. A growing body of evidence indicates that MVOCs are ecofriendly and can be exploited as a cost-effective sustainable strategy for use in agricultural practice as agents that enhance plant growth, productivity and disease resistance. As naturally occurring chemicals, MVOCs have potential as possible alternatives to harmful pesticides, fungicides and bactericides as well as genetic modification. Recent studies performed under open field conditions demonstrate that efficiently adopting MVOCs may contribute to sustainable crop protection and production. We review here the chemical diversity of MVOCs and their potential physiological effects on crops and analyze potential and actual limitations for MVOC use as a sustainable strategy for improving productivity and reducing pesticide use.